PENGARUH TINGKAT PENDIDIKAN, KEPADATAN PENDUDUK DAN KETIMPANGAN PENDAPATAN TERHADAP KRIMINALITAS DI INDONESIA - Adek Oktaviani Edwart; Zul Azhar (Jurnal Kajian Ekonomi dan Pembangunan, 2019)
This study aims to determine: (1)TVC XDFGhe Influence of Education Levels against Crime in Indonesia. (2) Effect of Population Density against Crime in Indonesia. (3) Effects  of Income Inequality on Crime in Indonesia. (4) Effect of Education Levels, Population Density, and Joint Income Inequality against Crime in Indonesia. The type of data used is secondary data. this study uses panel data, which uses 31 provinces in Indonesia using the Random Effect Model (REM) approach. The results of this study indicate that: (1) Education levels have a positive and significant effect on crime in Indonesia. (2) Population density has a negative and significant effect on crime in Indonesia. (3) Income inequality has a positive and not significant effect on crime in Indonesia. Based on the results of this study, it is expected that the goverment and the authorities will actively carry out socialization aimed at creating security and order in areas prone to criminal acts and implementing programs for equitable development and creating employment opportunities to improve the economy of the community.